Evaluation of an Information System using the PIECES Framework: A Case Study of the Inventory Administration Information System (SIAP) of the North Sulawesi Provincial Government - Aruperes, Viveca Grivenda; Hartomo, Kristoko Dwi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
This study evaluates user satisfaction with the Inventory Administration Information System (SIAP) in North Sulawesi Province using the PIECES Framework and provides recommendations for improvement. The PIECES Framework was chosen due to its proven effectiveness in assessing satisfaction, identifying issues, and guiding system development. This framework consists of six variables: Performance, Information & Data, Economic, Control & Security, Efficiency, and Service. The sample size was determined using Slovin's formula, involving 36 administrators from government offices. Data was collected through questionnaires measured on a Likert scale. The results indicate overall user satisfaction across all six variables. However, some weaknesses were identified, particularly in the Performance and Control & Security variables.